The Micro Economy Today - Schiller, Bradley R. (McGraw-Hill, 2006)
Brad Schiller's text, The Microeconomy Today, 10/e, is noted for three great strengths: readability, policy orientation, and pedagogy. His accessible writing style engages students and brings some of the excitement of domestic and global economic news into the classroom. Schiller emphasizes how policymakers must choose between government intervention and market reliance to resolve the core issues of what, how, and for whom to produce. This strategic choice is highlighted throughout the full range of micro, macro, and international issues. Every chapter ends with a policy issue that emphasizes the markets vs. government dilemma. And Schiller packs his chapters with the facts of economic life—real stories and applications, not fables. This is a book that teaches economics in a relevant context with careful pedagogy. Schiller 10e is for students motivated by real-world policy issues who want to become economically literate. This is a book students actually READ. Schiller is also known for its cutting-edge and current coverage of today’s issues.